The Impact of the Realization of Village Fund Sources, the Realization of Village Fund Allocation Sources, and the Realization of Village Original Income Sources on the Realization of Village Budget Expenditure - Sparta, Sparta; Nuraeni, Dini (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
This study aims to analyze the effect of village fund, village fund allocations, and village original revenue on village expenditures. The population in this research consists of the village income and expenditure budget reports from 2018 to 2022 across all villages in West Java Province, as published by Badan Pusat Statistik Indonesia. The hypothesis testing results indicate that village fund have a significant positive impact on village expenditures, suggesting that the realization of village fund has been carried out in accordance with their objectives, thereby improving the standard of living and enhancing community welfare. Village fund allocations also have a significant positive effect on village expenditures, indicating that the allocation of these funds is being implemented in line with priorities aimed at fostering the development needed by village communities. Additionally, village original revenue significantly positively influences village expenditures, suggesting that villages in West Java Province are effectively optimizing local resources to meet their expenditure requirements.